The Transformation of Islamic Epistemology in Technology Education: A Case Study of Computer Science at Universitas Muhammadiyah Kudus - Toni Ardi Rafsanjani; Waston; Kani Ulger (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to critically evaluate the application of Islamic integrative epistemology in the Computer Science Study Program at the University of Muhammadiyah Kudus, focusing on the extent to which Islamic values are internalized in the curriculum, teaching methods, and academic culture. Theoretical framework: This study uses the Islamic integrative epistemological framework as an effort to answer epistemological concerns that arise due to the dominance of dichotomous and positivistic paradigms, especially in non-religious disciplines such as Computer Science. This epistemology seeks to harmonize Islamic science and general science in a coherent set of values. Literature review: The literature review includes a discussion of epistemological crises in modern higher education, technocratic tendencies in the development of exact science, and the concept of scientific integration in an Islamic perspective. Emphasis is also placed on the importance of instilling moral and spiritual values in learning in Islamic universities. Methods: This study uses a qualitative approach with a case study design. The data collection technique was carried out through in-depth interviews, participatory observations, and documentation analysis of academic activities within the Computer Science Study Program, University of Muhammadiyah Kudus. Results: The results of the study show that efforts to integrate Islamic values in the development of Computer Science are still symbolic and fragmented. The main obstacles stem from the low epistemological awareness among academics and the strong dominance of technocratic approaches. Nevertheless, there are promising integration opportunities in courses such as Professional Ethics and Islamic Religious Education, which can be developed through a reflective and transdisciplinary pedagogical approach. Implications: A reformulation of value-based curriculum, improved epistemological literacy, and cross-disciplinary synergy are needed to encourage more substantial scientific integration in Islamic universities. Novelty: This study presents a new perspective on the application of Islamic epistemology in Computer Science, with an emphasis on the deep integration of values to form graduates who are both technological and have Islamic character.